Kegunaan Model CIPP dalam Evaluasi Pendidikan Inklusi - Arni, Irada Haira; Gunawan, Gunawan; Fatwa, Bunga; Sentoso, Ilham (MASALIQ, 2021)
Inclusion..education..in..the..modern..era..as..it..is..today becomes a very important thing in the world of Education. Therefore,..this study was conducted to find out the usefulness of the CIPP model in the expansion of inclusion education programs. In the process of evaluation of inclusion education, this CIPP model consists of 4 steps, namely: 1) context evaluation, conducted to set curriculum objectives, 2) input evaluation, determining the selection of strategies and teaching methods to be used, 3) evaluation of the process, conducting the selection of the learning process and solving existing problems, 4) product evaluation, is the result of the achievement of a program. In this study, researchers used the research method of literature studies in finding data related to the problem topic.